What if young z > 9 JWST galaxies hosted massive black holes? - Volonteri, Marta; Habouzit, Mélanie; Colpi, Monica (Monthly notices of the Royal Astronomical Society, 2023)
JWST is discovering star-forming ‘candidate’ galaxies with photometric redshifts z > 9 and little attenuation. We model presumptive massive black holes (MBHs) in such galaxies and find that their unobscured emission is fainter than the galaxy starlight in JWST filters, and difficult to be detected via colour-colour selection, and X-ray and radio observations. Only MBHs overmassive relative to expected galaxy scaling relations, accreting at high Eddington rates, would be detectable. Their discovery would point to the presence of heavy MBH seeds, but care is needed to exclude the existence of lighter seeds as only overmassive MBHs are detectable in this type of galaxies. Conversely, if no overmassive MBHs are hosted in these galaxies, either there are no heavy seeds or they are rare. The most massive/highest redshift candidate galaxies can attain stellar masses in excess of $5\times 10^{10}\, {\rm M_\odot }$ by z ∼ 6 if they grow along the star formation rate-mass sequence, and can nurse an MBH growing from ${\sim}10^5 \, {\rm M_\odot }$ up to ${\gt}3\times 10^7\, {\rm M_\odot }$ by z ∼ 6, to become hosts of some z > 6 quasars. Candidate galaxies of $\log (M_{\rm gal}/\, {\rm M_\odot })\sim 8$ cannot grow their putative seeds fast, unless seeds are ${\gtrsim}10^6\, {\rm M_\odot }$. The number density of the JWST candidate galaxies far outnumbers that of the highest z quasar hosts and this allows for about only one bright z ∼ 6-7 quasar every 1000 of these galaxies.
Gesehen am 26.05.2023